ECONOMIC SECURITY OF INNOVATIVE ENTERPRISES: ASSESSMENT RESULTS AND DIRECTIONS FOR STRENGTHENING - ZHADKO, Kostiantyn; OSTAPCHUK, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article deals with the aspects of analyzing, assessing and ensuring the economic security of an enterprise. The relevance and specific aspects of managing and ensuring the economic security of innovatively active business entities are indicated. Such business entities face a new group of risks and threats related to the field of intellectual property, i.e. regarding the preservation of trade secrets, combating crimes in the field of protection and protection of intellectual property objects, information handling and ensuring information and cyber security, forming a reliable system of protection of rights to inventions, utility models, commercial designations, etc. Therefore, this imposes its own specifics both during the analysis and management of the economic security of innovatively active enterprises and organizations. The purpose of the study was to assess and identify areas for strengthening economic security using the example of one of the innovatively active enterprises. The state of the following components of the enterprise's economic security was analyzed, as financial, intellectual and personnel, technical and technological, political and legal, environmental, information, product, and power. Conclusions are drawn in the context of guaranteeing the economic security of an innovatively active enterprise. The directions of ensuring the economic security of an innovatively active business entity have been determined. The scientific novelty of the research results lies in linking the processes of innovative development of business entities and ensuring their economic security. The practical significance lies in developing proposals to eliminate threats to the innovative activity of the enterprise.
Keywords: enterprise economics; enterprise management; innovative development; innovative activity; economic security; assessment methodology; directions of strengthening security